2016
DOI: 10.1542/peds.137.supplement_3.593a
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes Following Nonoperative Versus Operative Treatment of Clavicle Fractures in Adolescents

Abstract: Purpose Superiority of non-operative versus operative treatment of clavicle shaft fractures remains unclear. We aimed to assess shoulder function in adolescents following shortened clavicle fracture and compare operative versus non-operative treatment.Methods Patients aged 12 to 18 years at the time of fracture and minimum 1.5 years post injury were identified for this institutional review board (IRB)-approved study. For this retrospective cohort study, patients were frequency-matched for age, gender, shorteni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Finally, seven studies were deemed eligible for the synthesis of the quantitative data [1,3,4,[17][18][19][20]. The seven studies included a total of 522 patients (with 528 mid-diaphyseal clavicle fractures) with an age range of 8 to 18 years, 148 underwent operative management, and 380 underwent nonoperative management.…”
Section: Search Strategy and Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, seven studies were deemed eligible for the synthesis of the quantitative data [1,3,4,[17][18][19][20]. The seven studies included a total of 522 patients (with 528 mid-diaphyseal clavicle fractures) with an age range of 8 to 18 years, 148 underwent operative management, and 380 underwent nonoperative management.…”
Section: Search Strategy and Study Characteristicsmentioning
confidence: 99%
“…The study characteristics are depicted in Table 1. Across the 6 studies that reported gender, there were 335 males and 109 females [3,4,[17][18][19][20]. Patients were followed up from 2 weeks to 3.7 years across five studies that reported follow-up time [1,3,4,19,20].…”
Section: Search Strategy and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the adolescent population, the existing body of evidence is insufficient to support the use of routine operative management. Although there is some evidence to support an earlier return to function, 6,31 the largest study reviewed indicated that there was no benefit observed with operative intervention. 23 Regarding adult fractures, it is difficult to interpret the apparently contradictory findings contained in the literature over the last two decades.…”
Section: Discussionmentioning
confidence: 99%
“…Herzog et al 31 conducted a retrospective study on 20 patients. The patient cohort was followed from the time of their injury for a year and a half.…”
Section: Concluded That Operative Fixation Improved Functional Outcom...mentioning
confidence: 99%